Allusions to scripture in the psalms of Solomon textual tradition, interpretation, and historical implications - Joosten, Jan 1959-; Brepols N.V. (Turnhout Brepols, 2024)
"Like other Jewish works from the late Second Temple period, Psalms of Solomon alludes constantly to passages in Scripture - particularly the Pentateuch, the Prophetic books and Psalms. Gathering all passages where the Psalms of Solomon refer to a specific verse in Scripture, the present monograph ventures to analyze the authors’ use of Scripture and to identify the textual tradition underlying the allusions. The conclusion this leads to is that the authors used a Greek version, close to the Septuagint but sporadically revised on the basis of the proto-Masoretic Hebrew text. This conclusion agrees with recent research on revisionary work on the Septuagint, which must have begun in the first century BCE, long before the named recensions of the second century CE (Aquila, Symmachus, Theodotion). The textual analysis casts a new light on the Psalms of Solomon. Although they came into being in Jerusalem in the aftermath of Pompey’s conquest of the city in 63 BCE, they were not composed in Hebrew, but in Greek. The identity of the Greek-speaking group that produced the Psalms of Solomon, and their religious views, are discussed in the final chapter of this monograph."
Literaturverzeichnis: Seite 137-145
Archivierung/Langzeitarchivierung gewährleistet